New Educational Technologies and Tools in Future Teachers’ Preparing for Professional Activities in a Multicultural Society - Boychuk, Yuriy; Berezhna, Svitlana; Yuryeva, Kateryna ("Intercultural Dialogues" Transactions, 2021)
Ethno-cultural diversity of the population of Ukraine actualizes the problem of preparing future teachers and educators for professional activities in a multicultural society. The legislative, normative, and conceptual framework of intercultural education in Ukraine is listed. The achievements of international organizations have been taken into account and creatively developed: UN, UNESCO, UNICEF, The Council of Europe. The author’s approach to the interpretation of the essence of intercultural competence is revealed, which provides the teacher with the ability to understand and respect the cultural diversity of modern Ukrainian society, understand its value as a resource for the development of personality and society, and use in practice the educational and socializing potential of cultural diversity. The structure of the intercultural competence is outlined, which combines personal-psychological, cognitive, procedural-activity components. The model of the formation of future teachers’ intercultural competence was developed and implemented at the H. S. Skovoroda Kharkiv National Pedagogical University. The model assumes the construction of the content of the process of forming intercultural competence on the basis of a comparative acquaintance of future teachers with the traditional culture of different peoples and its implementation in the educational process, pedagogical practices, extracurricular and research activities of students; the use of innovative forms, methods and techniques of work: interactive, training, game, project; purposeful impact on the emotional sphere of the student's personality (work with moral dilemmas and multimedia resources); creation of an educational environment for intercultural communication in a pedagogical university. The media resources used in the process of forming the intercultural competence of future teachers (films of the Docudays festival, cartoons of the “Lullabies of the Worldˮ project, clips of the video project “Made in Ukraineˮ, etc.), as well as digital tools (virtual interactive whiteboards Padlet, Google Jamboard, service for creating presentations and instant polls Mentimeter, an online tool for creating interactive Wordwall games).